Micronutrient intakes in enterally and orally fed children with severe cerebral palsy - Schoendorfer, N.; Tinggi, U.; Sharp, N.; Boyd, Roslyn; Vitetta, L.; Davies, P. (2011)
Background & aims: This study aims to investigate micronutrient balance in children with Cerebral Palsy (CP), due to a paucity of this literature and their well documented issues with undernutrition. Methods: Twenty-one children aged 4-12 years with marked CP fed orally (O, n = 12) or enterally (PEG, n = 9) were recruited, including age matched typically developing children (C, n = 16). Parents collected three consecutive days food replica of their child's actual intake and the contents directly analysed. Values were calculated as percentage (%) of Estimated Average Requirement (EAR) or Adequate Intake (AI) where applicable. Results: Micronutrient intakes varied widely. Significant differences were found for Zinc: mean(±SD%) between PEG = 379(153) versus both O = 185(67) and C = 171(54) p < 0.001 and Iron: PEG = 311(93) versus O = 110(54) and C = 179(108), p = 0.001 and Copper: PEG = 162(±70); O = 44(±30); C = 78(±23) p < 0.001. Many O and C consumed insufficient iodine or calcium, including less than AI in potassium and manganese. Sodium intakes in 6/16 C were in excess of upper safety limits and 4/9 PEG consumed excessive Zinc. Conclusions: Micronutrients have the potential to competitively inhibit one another in excess or deficiency through limiting their metabolism. In light of this, further investigations should assess the physiological impact of dietary imbalances, particularly in populations with limitations in their food consumption. © 2011 European Society for Clinical Nutrition and Metabolism.